THE INFLUENCE OF FIRST LANGUAGE ON THE PRONUNCIATION OF SECOND LANGUAGE (A CASE STUDY OF THE MEMBERS OF ENGLISH CLUB AT MTS SALAFIYAH SYAFIIYAH MUMBULSARI JEMBER) - Authar, Nailul (Universitas Nahdatul Ulama Surabaya, 2018)
The first language will always influence the second language acquisition. The influences involve all parts of language learning such language skills (speaking, reading, listening, and writing) and language components (vocabulary, grammar, and pronunciation). In particular, this current study focuses on investigating the influence of first language on the pronunciation of second language. It is found that there is a negative transfer got by most of the members of English club at MTS Salafiyah Syafiiyah Mumbulsari Jember. The respondents make more mistakes or errors because of the interference of their L1 to the L2 as a result of negative transfer. This paper is divided into seven parts. Those are introduction, the definition of LI and L2, the definition and features of pronunciation, research design, and pronunciation test given to the respondent, result, discussion, and conclusion.